Resin composition, resin film, and display device
The resin composition addresses the issues of flexibility and flatness in organic EL display devices by using a polymer with thermal crosslinking agents and a photosensitizer, enhancing bending recovery and reliability.
Patent Information
- Application Number
- JP2022542928
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-27
- Filing Date
- 2022-04-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-04-14
AI Technical Summary
Existing photosensitive resin compositions for organic electroluminescent (EL) display devices face issues with insufficient long-term reliability, low flexibility, and poor flatness, particularly in devices with curved surfaces that require better bending performance and resistance to scratching.
A resin composition comprising a polymer with specific structural components, including thermal crosslinking agents and a photosensitizer, which enhances flexibility and flatness by incorporating an aliphatic group with a siloxane structure and using aromatic ester and unsaturated bond-containing thermal crosslinking agents to improve heat resistance and chemical resistance.
The resin composition achieves improved flatness, bending recovery performance, and luminous efficiency in organic EL display devices, ensuring long-term reliability and flexibility.
Smart Images

Figure 0007612696000001 
Figure 0007612696000002 
Figure 0007612696000003
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present invention relates to a resin composition, a resin film formed from the resin composition, and a display device formed using the resin composition and / or the resin film.
[0002] [Background technology] In recent years, organic electroluminescent (hereinafter referred to as "organic EL") display devices have been widely used in many electronic devices. In general, an organic EL display device has a driving circuit, a planarization layer, a first electrode, an insulating layer, a light-emitting layer, and a second electrode on a substrate, and emits light by applying a voltage between the first electrode and the second electrode disposed on the opposite side, or by the flow of a current. In an organic EL display device, a photosensitive resin composition that can be used for patterning by ultraviolet irradiation is usually used as the material of the planarization layer and the material of the insulating layer.
[0003] As electronic devices become smaller, more functional, and more integrated, the performance requirements for electronic components used in the electronic devices are also increasing. For example, resins such as polyimide, polybenzoxazole, and polyamideimide have excellent properties in terms of heat resistance, electrical insulation, etc., and therefore photosensitive resin compositions containing such resins are suitable as materials for insulating layers or planarizing layers in organic electroluminescence display devices.
[0004] On the other hand, in an organic EL display device that is easily bent and includes a curved surface, the materials for the insulating layer and the planarizing layer are required to have better flatness and bending performance. Therefore, it is also very important to improve the flatness and bending performance of the photosensitive resin composition.
[0005] At present, it is known that phenolic hydroxyl compounds can be introduced into polyimide precursors in order to solve the problem of development failure in a short time and then improve the resolution of fine patterns. However, there are problems such as compound scattering during curing and thermal shrinkage (Patent Document 1). In addition, it is known that the introduction of a thermal crosslinking agent into a photosensitive resin precursor composition can reduce the thermal shrinkage rate, but the resulting photosensitive resin precursor composition has problems such as low bending resistance, scratches and wrinkles that are prone to occur (Patent Document 2).
[0006] [Prior art document] [Patent documents] [Patent Document 1: CN1246389C] [Patent Document 2: CN100362429C]
[0007] [Summary of the Invention] When the photosensitive resin precursor composition described in the above patent documents is used in an organic electroluminescence display device, many problems appear, such as poor long-term reliability, poor flexibility, and poor flatness, etc. Therefore, the technical solution in the present invention is mainly aimed at solving the above-mentioned problems.
[0008] According to an embodiment of the present invention, a resin composition including at least three components (a), (b) and (c) can be provided, in which the component (a) is a polymer having a structure represented by the following formula (1), the component (b) includes a thermal crosslinker (b1) and a thermal crosslinker (b2), and the component (c) is a photosensitizer;
[0009] [ka]
[0010] In the formula, R 1 and R 2 are independently selected from the group containing at least one atom other than hydrogen, R 3 and R 4are independently selected from a hydrogen atom or an organic group having 1 to 20 carbon atoms, and n is an integer selected from 1 to 10.
[0011] In another embodiment of the present invention, the thermal crosslinker (b1) is an aromatic ester thermal crosslinker and the thermal crosslinker (b2) is a thermal crosslinker containing an unsaturated bond. In another embodiment of the present invention, the thermal crosslinking agent (b1) is a low-temperature thermal crosslinking compound having a thermal crosslinking temperature of 120°C to 180°C, more specifically, selected from the structure represented by the following formula (2):
[0012] [ka]
[0013] In the formula, R 8 is selected from organic groups containing 2 to 30 carbon atoms; R 9 is selected from an organic group containing 1 to 10 carbon atoms, s is an integer selected from 1 to 4, p is an integer selected from 1 to 16, and s+p>2.
[0014] In another embodiment of the present invention, the thermal crosslinking agent (b2) is selected from a thermal crosslinking compound having a thermal crosslinking temperature of 180°C to 400°C, more specifically, a structure represented by the following formula (3) and / or a structure represented by the following formula (4):
[0015] [ka]
[0016] In the formula, R 6 and R 7 are independently selected from organic groups containing at least 2 to 30 carbon atoms, and y and q are independently integers selected from 1 to 10.
[0017] In another embodiment of the present invention, the structure represented by formula (3) is a structure containing acrylic acid, more specifically, selected from one or more structures represented by the following formula (5):
[0018] [ka]
[0019] In the formula, R 10 is selected from organic groups containing 2 to 25 carbon atoms, and z is an integer selected from 1 to 10. In another embodiment of the present invention, component (a) is a polymer having a structure represented by formula (6):
[0020] [ka]
[0021] In the formula, R 1 and R 2 are independently selected from the group containing at least one atom other than hydrogen, R 3 and R 4 are independently selected from a hydrogen atom or an organic group having 1 to 20 carbon atoms; R 5 is selected from halogen and / or halogenated hydrocarbyl, and / or organic groups having 1 to 10 carbon atoms; and n and m are independently integers selected from 1 to 10.
[0022] Other embodiments of the present invention may include one or more of polyamides, polyimides, polyimide precursors, polybenzoxazoles, polybenzoxazole precursors, or copolymers thereof.
[0023] In another embodiment of the present invention, the photosensitizer of component (c) is a photoacid generator. In another embodiment of the present invention, phenolic hydroxyl compounds are also included.
[0024] According to another embodiment of the present invention, there may be provided a resin film prepared from the photosensitive resin composition of the present invention. According to another embodiment of the present invention, a display device prepared from the resin composition of the present invention or including the resin film of the present invention may be provided.
[0025] In another embodiment of the present invention, the composition may further include a component (a1), where the component (a1) includes an aliphatic group having a siloxane structure. Preferably, the component (a1) includes a structure represented by formula (7):
[0026] [ka]
[0027] In the formula, R 11 is an organic group containing at least 1 to 20 Si-O repeating units, and also includes an aliphatic group. In another embodiment of the present invention, R 11 is selected from one or more of the structures shown below:
[0028] [ka] .
[0029] In another embodiment of the present invention, the weight ratio of the component (a1) is 0.01 wt % to 10 wt % with respect to the component (a). In another embodiment of the present invention, R 1 may be selected from one or more of the structures shown below:
[0030] [ka] .
[0031] In another embodiment of the present invention, R 1 may further be selected from one or more of the structures shown below:
[0032] [ka] .
[0033] In another embodiment of the present invention, R 2 may be selected from one or more of the structures shown below:
[0034] [ka] .
[0035] Considering the degree of refinement of the figure, R 2 The residue comprising preferably has the structure shown below:
[0036] [ka] .
[0037] In another embodiment of the present invention, the thermal crosslinker (b1) may be specifically selected from one or more of the following compounds:
[0038] [ka] .
[0039] In another embodiment of the present invention, the thermal crosslinker (b1) may be more specifically selected from one or more of the following compounds:
[0040] [ka] .
[0041] In another embodiment of the present invention, the thermal crosslinker (b2) may be specifically selected from one or more of the following compounds:
[0042] [ka] TIFF0007612696000015.tif163170.
[0043] After intensive research, the inventors have found that by using the resin composition of the present invention, it is possible to obtain an organic EL display device having better flatness and bending recovery performance, and thus good luminous efficiency and flexibility.
[0044] Detailed Description of the Embodiments In order to make the objectives and advantages of the present invention clearer, the technical solutions of the present invention will be described more clearly and completely in the following in combination with the embodiments of the present invention. Obviously, the described embodiments are only a small part of the embodiments of the present invention, and are intended to help those skilled in the art to further understand the present invention, but do not limit the present invention in any way. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without any creative efforts shall fall within the scope of protection of the present invention.
[0045] <Resin composition> The resin composition of the present invention can include at least three components (a), (b) and (c), where component (a) is a polymer having a structure represented by formula (1), component (b) includes a thermal crosslinker (b1) and a thermal crosslinker (b2), and component (c) is a photosensitizer.
[0046] Component (a) is a polymer having a structure represented by formula (1), which contains alkali-soluble groups such as hydroxyl and can be called an alkali-soluble polymer.
[0047] [ka]
[0048] In the formula, R 1 and R 2 are independently selected from the group containing at least one atom other than hydrogen, R 3 and R4 are independently selected from a hydrogen atom or an organic group having 1 to 20 carbon atoms, and n is an integer selected from 1 to 10.
[0049] R 1 and R 2 The atoms other than hydrogen contained in R are preferably independently selected from one or more of O, S, N, P, B, Si1 to Si20, and C1 to C30. In consideration of the flexibility of the polymer, R 1 is more preferably selected from the group not containing an aromatic hydrocarbyl group but containing one or more of O, S, N, and C atoms. In consideration of the heat resistance of the polymer, R 2 is more preferably selected from the group comprising aromatic and / or heteroaromatic groups, R 2 It is more preferable that the aromatic and / or heterocyclic aromatic groups in R are on the main chain of the polymer. 2 It is further preferred that the hydroxyl group is directly bonded to the aromatic and / or heteroaromatic group. Polymer (a) can also include polymers having a structure represented by formula (6), where R 5 is R 2 In addition, R 5 can be selected from halogen, and / or halogenated hydrocarbyl, and / or organic radicals having 1 to 10 carbon atoms, and taking into account the degree of refinement of the formed pattern, R 5 is preferably selected from halogen and / or halogenated hydrocarbyl groups bearing electron withdrawing groups, and n and m are independently integers selected from 1 to 10.
[0050] [ka]
[0051] The polymer having the structure represented by formula (1) and / or formula (6) provided by the present invention can be obtained by polymerizing raw materials such as acid dianhydride and diamine, etc. For example, a method of reacting acid dianhydride with a diamine compound in a solvent can be mentioned.
[0052] R used in polymer (a) 1 As the residue of an acid dianhydride containing the formula:
[0053] [ka] .
[0054] Considering the flexibility of the polymer, R 1 has the structure of the following group, which has relatively little steric hindrance:
[0055] [ka] .
[0056] R 1 Specific examples of the acid dianhydride include the following compounds:
[0057] [ka] .
[0058] R used in polymer (a) 2 As the residue of a diamine containing the above, the following structure can be specifically mentioned:
[0059] [ka] .
[0060] Considering the degree of refinement of the figure, R 2The diamine residue containing structure preferably has the structure shown below:
[0061] [ka] .
[0062] R 2 As diamines containing the formula, the following compounds can be specifically listed:
[0063] [ka] .
[0064] In another embodiment of the present invention, in consideration of controlling the polymer molecular weight and the distribution of the polymer molecular weight, the molar ratio of the acid dianhydride to the diamine is preferably 35:65 to 65:35, more preferably 40:60 to 60:40, and even more preferably 45:55 to 55:45.
[0065] In other embodiments of the present invention, the resin composition may include one or more of polyamides, polyimides, polyimide precursors, polybenzoxazoles, polybenzoxazole precursors, or copolymers thereof.
[0066] The acid dianhydrides and diamines in the present invention can be used alone or in combination. Unless otherwise specified, the acid dianhydrides and diamines in the present invention can both be synthesized by known methods.
[0067] Furthermore, in order to further increase the flexibility of the resin composition, a component (a1) containing an aliphatic group having a siloxane structure can also be introduced into the resin composition, where the compound containing an aliphatic group having a siloxane structure used is not specifically limited. In consideration of the dispersion effect and improvement of flexibility after addition, it is preferably selected from the structure represented by formula (7):
[0068] [ka]
[0069] In the formula, R 11 is an organic group containing at least 1 to 20 repeating units of Si-O, and R 11 R may also contain an aliphatic group bonded to the siloxane in a copolymerized manner, with preferred aliphatic groups having C1 to C30 carbon atoms. In consideration of the warpage properties of the polymer, R 11 The weight average molecular weight ranges from 10 to 5,000.
[0070] Specifically, R 11 can be exemplified by one or more of the structures shown below:
[0071] [ka] .
[0072] R 11 is preferably
[0073] [ka] The compound has a structure represented by:
[0074] The structure represented by formula (7) contained in component (a1) can be obtained from a terminal compound having a diamine, and can be specifically exemplified by the following compound:
[0075] [ka] .
[0076] The structure represented by formula (7) contained in component (a1) can be obtained from a terminal compound having diamine, and the method of addition is not particularly limited. The terminal compound having diamine can be directly mixed with polymer (a), or can be introduced into the main chain and / or branched chain of polymer (a) through polymerization reaction, that is, it can participate in the polymerization reaction using diamine as a raw material, and therefore can be introduced into the polymer chain of polymer (a).
[0077] For the purpose of further increasing the flexibility of the resin composition, the amount of the aliphatic group-containing compound having a siloxane structure added preferably accounts for 0.01 wt % to 10 wt % of the total polymer.
[0078] (b) Thermal crosslinking agent The component (b) contained in the resin composition of the present invention is an aromatic ester thermal crosslinker (b1) and a thermal crosslinker containing unsaturated bond (b2).In general, the crosslinker can improve the heat resistance and chemical resistance of the cured film formed from the resin composition, and further, in the present invention, it should be shown that the thermal crosslinker is used to improve the flatness of the cured film, and achieve better performance and better yield when manufacturing the device.
[0079] The aromatic ester thermal crosslinking agent (b1) used as the thermal crosslinking agent in the present invention is preferably selected from low-temperature thermal crosslinking compounds having a crosslinking temperature of 120°C to 180°C, and specifically, may be a compound represented by the following formula (2).
[0080] [ka]
[0081] In formula (2), R 8 is selected from organic groups containing 2 to 30 carbon atoms; R 9is selected from organic groups containing 1 to 10 carbon atoms, s is an integer selected from 1 to 4, p is an integer selected from 1 to 16, and s+p>2. In order to achieve a better thermal crosslinking effect, formula (2) can be further preferably limited. Preferably, s is an integer of 2 to 4, preferably, p is an integer of 2 to 6, and preferably, R 8 is a structure containing an aromatic group or a heterocyclic aromatic group. In addition, the phenolic hydroxyl group described in formula (2) can be protected by esterification without affecting the thermal crosslinking properties, which is also part of the present invention.
[0082] Specifically, the aromatic ester thermal crosslinker as the thermal crosslinker (b1) can be exemplified by one or more of the compounds shown below:
[0083] [ka] .
[0084] For the aromatic ester thermal crosslinker as thermal crosslinker (b1), it is preferably selected from one or more compounds having the following structure:
[0085] [ka] .
[0086] The unsaturated bond thermal crosslinking agent used in the present invention as the thermal crosslinking agent (b2) is preferably selected from thermal crosslinking compounds having a thermal crosslinking temperature of 180° C. to 400° C. Specifically, it may be selected from one or more compounds represented by the following formula (3) and / or formula (4):
[0087] [ka]
[0088] In the formula, R 6 and R 7are independently selected from organic groups containing 2 to 30 carbon atoms, and y and q are integers independently selected from 1 to 10. 6 In addition to carbon atoms, the compound represented by formula (3) may contain other heteroatoms such as O and N, and preferably contains an acrylic acid structure, specifically, one or more compounds represented by the following formula (5):
[0089] [ka]
[0090] In the formula, R 10 is selected from organic groups having 2 to 25 carbon atoms, and z is an integer selected from 1 to 10. In consideration of the thermal crosslinking effect, z is more preferably an integer selected from 2 to 8, and further, R 10 may or may not contain an aromatic structure, and both have good thermal crosslinking properties.
[0091] In consideration of the thermal crosslinking effect, in the compound represented by formula (4), q is preferably an integer selected from 1 to 6, and R 7 is preferably selected from structures containing an aromatic ring.
[0092] Specifically, in the thermal crosslinking agent containing an unsaturated bond as the thermal crosslinking agent (b2), the compound represented by formula (3) and / or formula (4) can be specifically exemplified by one or more of the following compounds:
[0093] [ka] TIFF0007612696000034.tif222170TIFF0007612696000035.tif28170.
[0094] The present invention is not particularly limited to the synthesis method of the thermal crosslinker. Unless otherwise specified, known methods can be used for synthesis. The content of the thermal crosslinking agent is not particularly limited. The content of the thermal crosslinking agent is preferably 10 to 40 parts by mass, more preferably 12 to 35 parts by mass, even more preferably 14 to 30 parts by mass, and particularly preferably 16 to 26 parts by mass, relative to 100 parts by mass of the total amount of the component (a) in the resin composition. The ratio of parts by mass of (b1) to parts by mass of (b2) is preferably 25:1 to 5:1, more preferably 22:1 to 8:1, and even more preferably 20:1 to 10:1.
[0095] (c) Photosensitizer The photosensitizer (c) contained in the resin composition of the present invention is not particularly limited. As the photosensitizer, a photopolymerization initiator and / or a photoacid generator that absorbs a specific wavelength and then decomposes to generate free radicals can be used. In the present invention, a photoacid generator is preferred.
[0096] Examples of photoacid generators in the photosensitizer in the resin composition include quinone diazide compounds, sulfonium salts, phosphonium salts, diazonium salts, iodonium salts, etc. In terms of long-term reliability of the organic EL device, photoacid generators containing quinone diazide compounds are preferred.
[0097] Examples of quinone diazide compounds include compounds obtained in the form of esters by binding sulfonic acid of diazidoquinone to polyhydroxy compounds, compounds obtained in the form of sulfamides by binding sulfonic acid of diazidoquinone to polyamine compounds, compounds obtained in the form of esters and / or sulfamides by binding sulfonic acid of diazidoquinone to polyhydroxypolyamine compounds, etc. All functional groups of these polyhydroxy compounds, polyamino compounds, and polyhydroxypolyamino compounds do not need to be completely substituted with diazidoquinone, and it is preferable that 40 mol% or more of the total functional groups are substituted with diazidoquinone on average. By including the quinone diazide compound, the affinity of the quinone diazide compound for an alkaline aqueous solution is reduced and the ratio of the dissolution rate of the exposed portion of the composition to the unexposed portion is increased, thereby making it possible to obtain a pattern with high resolution and to obtain a positive photosensitive resin precursor composition that is photosensitive to the i-line (wavelength 365 nm), h-line (wavelength 405 nm), and g-line (wavelength 436 nm) of a typical ultraviolet mercury lamp.
[0098] In the present invention, there is no particular limitation on the type and synthesis method of the quinone diazide compound as a photosensitizer. Unless otherwise specified, known quinone diazide compounds and their synthesis methods can be used. The quinone diazide compounds can be used alone or in combination. Therefore, the ratio of the dissolution rate of the exposed part to the unexposed part can be further increased, and a highly sensitive photosensitive resin precursor composition can be obtained.
[0099] The content of the photosensitizer is not particularly limited, and is preferably 10 to 50 parts by mass, more preferably 20 to 40 parts by mass, relative to 100 parts by mass of the total amount of component (a) in the resin composition. By setting the content of the photosensitizer within this range, high sensitivity can be achieved, and the sensitizer can be further contained as necessary.
[0100] In addition to the polymer (a), the thermal crosslinker (b), and the photosensitizer (c), the resin composition of the present invention may also contain the following additives. (d) Solvent The resin composition of the present invention may contain an organic solvent. By adding the solvent, the three components (a), (b) and (c) can be completely and uniformly dispersed, and each component can be dissolved in the solvent and prepared into a varnish form, thus further improving the properties such as coating properties of the resin composition.
[0101] The organic solvent in the resin composition is not particularly limited. Examples of the organic solvent include ethers, acetates, esters, ketones, aromatic hydrocarbons, amides, and alcohols. More specifically, γ-butyrolactone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol mono-n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol, monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol mono-n-butyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol mono-n-butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol monomethyl ether, tripropylene ether, tetrahydrofuran, dioxane, tetramethyl ether, tetramethyl ether, tetraethyl ether, tetramethyl ...ethyl ether, tetramethyl ether, tetraethyl ether, tetraethyl ether, tetramethyl ether, tetraethyl ether, tetraethyl ether, tetraethyl ether, tetraethyl ether, tetraethyl ether, tetraethyl acetone, methyl ethyl ketone, diisobutyl ketone, cyclohexanone, 2-heptanone, 3-heptanone, diacetone alcohol, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl 2-hydroxy-2 -Methyl propionate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-ethoxypropionate, ethyl ethoxyacetate, ethyl hydroxyacetate, methyl 2-hydroxy-3-methylbutyrate, 3-methoxybutyl acetate, methoxybutyl 3-methyl-3-acetate, 3-methyl-3-methoxybutylpropionate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate,Isobutyl acetate, n-amyl formate, isoamyl acetate propyl valerate n-butyl ester, ethyl butyrate, n-propyl butyrate, butyrate isobutyric acid, n-butyl butyrate, methyl pyruvate, ethyl pyruvate, n-propyl pyruvate, methyl acetoacetate, ethyl acetoacetate, ethyl 2-oxobutanate, aromatic compounds (e.g., toluene and / or xylene), amides (e.g., one or more of hydrocarbyl, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, etc.). One or more of these may be included.
[0102] The content of the solvent is not particularly limited. In order to dissolve the composition, the content of the solvent is preferably 100 to 2000 parts by mass, more preferably 300 to 1700 parts by mass, even more preferably 400 to 1200 parts by mass, and particularly preferably 600 to 1100 parts by mass, relative to 100 parts by mass of the total amount of the component (a) excluding the solvent in the resin composition. According to the requirements of the coating process, resin composition solutions having various viscosities can be prepared by adjusting the content of the polymer, and a resin film having excellent performance can be obtained in a better way. Preferably, the viscosity of the resin composition solution is in the range of 0.1 to 12000 cP, more preferably 0.5 to 10000 cP, and more preferably 1 to 8000 cP.
[0103] (e) Endcapping agent In order to adjust the molecular weight of the resin composition to a preferred range, both ends can be terminated with an endcapping agent. Examples of endcapping agents in the reaction with an acid dianhydride compound include monoamines and monohydric alcohols. Examples of endcapping agents in the reaction with a diamine compound include anhydrides, monocarboxylic acids, monoacid chloride compounds, monoactive ester compounds, dicarbonate compounds, vinyl ether compounds, and the like. In consideration of the endcapping effect and heat resistance, it is preferable that the endcapping agent contains an aromatic functional group. Furthermore, by obtaining other good effects, various functional organic groups can also be introduced into the endcapping agent as terminal groups. For example, the introduction of an alkali-soluble functional group such as hydroxyl or carboxyl can improve its alkali-soluble properties, and the introduction of an unsaturated bond can improve its thermal crosslinking properties, etc. It is even more preferable that the introduced functional organic group is linked to an aromatic ring in the endcapping agent to obtain better performance.
[0104] The content of the endcapping agent is not particularly limited, and is preferably 0.1 to 20 parts by mass, more preferably 0.8 to 15 parts by mass, and even more preferably 1.0 to 10 parts by mass, relative to 100 parts by mass of the total amount of component (a) in the resin composition. By setting the content of the endcapping agent within this range, a good endcapping effect can be obtained without excess organic matter remaining in the resin composition.
[0105] (f) Phenolic hydroxyl compounds The resin composition of the present invention may also contain a compound having a phenolic hydroxyl group as an additive. By containing a compound having a phenolic hydroxyl group, the alkaline solubility of the polymer can be improved better, and thus the development time can be shortened. In detail, the resin composition obtained by using a compound having a phenolic hydroxyl group is basically insoluble in an alkaline developer before exposure, and when exposed, the resin composition is easily dissolved in an alkaline developer and easily developed in a short time. Therefore, the film loss caused by development is small. Therefore, a finer relief pattern can be obtained.
[0106] The phenolic hydroxyl compound may be, in addition to the various compounds containing a phenolic hydroxyl group described above, bis(Bis)-Z, bis(Bis)OC-Z, bis(Bis)OPP-Z, bis(Bis)P-CP, bis(Bis)26X-Z, bis(Bis)OTPB-Z, bis(Bis)OCHP-Z, bis(Bis)OCR-CP, bis(Bis)P-MZ, bis(Bis)P-EZ, bis(Bis)26X-CP, bis(Bis)P-PZ, bis(Bis) s)P-IPZ, BisCR-IPZ, BisOCP-IPZ, BisOIPP-CP, Bis26X-IPZ, BisOTPB-CP, TekP-4HBPA, TrisP-HAP, TrisP-PA, BisOFP-Z, BisRS-2P, BisPG-26X, BisRS-3P, BisOC-OCHP, BisPG-26X , BisPC-OCHP, Bis26X-OCHP, BisPG-26X, BisOCHP-OC, Bis236T-OCHP, BisRS-26X, BIR-OC, BIP-PC, BIR-PC, BIR-PTBP, BIR-PCHP, BIP-BIOC-F, BIR-BIPC-F, TEP-BIP-A, etc. can be listed, as well as Bis-Z, BisP-EZ, TekP-4 Preferred are HBPA, TrisP-HAP, TrisP-PA, BisOCHP-Z, BisP-MZ, BisP-PZ, BisP-IPZ, BisOCP-IPZ, BisP-CP, BisRS-2P, BisRS-3P, BisP-OCHP, BisRS-26X, BIP-PC, BIR-PC, BIR-PTBP, and BIR-BIPC-F. May include one or more of these. As described in the present invention, other structures or substances having phenolic hydroxyl groups can also be present as phenolic hydroxyl compounds.
[0107] Considering the heat resistance of the phenolic hydroxyl compound, bisphenol is preferred. The content of the phenolic hydroxyl compound is preferably 1 to 50 parts by mass relative to 100 parts by mass of the total amount of the resin composition. Therefore, it is possible to improve the alkali developability in the photosensitive resin precursor composition while maintaining high heat resistance.
[0108] The resin composition of the present invention may also contain at least one or two or more of polyamide, polyimide, polyimide precursor, polybenzoxazole, polybenzoxazole precursor, or copolymers thereof.
[0109] <Preparation of Resin Composition> The first step is the synthesis of a polymer. First, the diamine and acid dianhydride required by the present invention are placed in a solvent, and the polymerization reaction is carried out at -20°C to 150°C for 1 to 10 hours with stirring, during which an end-capping agent is added to form a polymer (a) having a target molecular weight. Then, an esterification agent is added to the solution system and reacted for 1 minute to 3 hours, and finally, the polymer is placed in water to obtain the target polymer.
[0110] In consideration of dissolution uniformity, the molecular weight of the polymer (a) is preferably in the range of 5,000 to 500,000, more preferably 8,000 to 350,000, and even more preferably 10,000 to 250,000.
[0111] In addition to the above-mentioned diamines and / or acid dianhydrides, the diamines and / or acid dianhydrides used in the present invention may also be combined with other common diamines and / or acid dianhydrides for the purpose of adjusting the performance of the polymer in order to obtain a resin film with better performance.
[0112] The esterification agent is not particularly limited. Unless otherwise specified, the esterification agent can be synthesized by using known methods. Specific examples include:
[0113] [ka] may include.
[0114] Considering the esterification effect and resin film forming performance, an esterification agent having a relatively low molecular weight is preferred for forming an esterification protecting group having a low molecular weight. The esterification agent is preferably selected from compounds having the following structure:
[0115] [ka] .
[0116] The solvent used in the polymerization step is not particularly limited as long as it can dissolve the acid dianhydride and diamine that act as raw material monomers. Specific examples of the amides include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolinone, N,N'-dimethylacrylurea, N,N-dimethylisobutyramide, and methoxy-N,N-dimethylpropionamide; cyclic esters include γ-butyrolactone, γ-pentalactone, δ-pentalactone, γ-caprolactone, ε-caprolactone, and α-methyl-γ-butyrolactone; carbonates include ethylene carbonate and propylene carbonate; diols include triethylene glycol; phenols include m-cresol and p-cresol; acetophenone, sulfolane, dimethyl sulfoxide, tetrahydrofuran, dimethyl sulfoxide, propylene glycol monomethyl ether acetate, and ethyl lactate.
[0117] The second step is the preparation of the varnish. First, the obtained target polymer is added to a solvent to dissolve it, and then the thermal crosslinker (b) and the photosensitizer (c) are added to the solution system. According to other functional requirements, some other additives may be added, for example, a phenolic hydroxyl compound is added to improve the alkaline dissolution performance, and finally obtain a varnish, also known as a resin composition. In consideration of the stability of the varnish, the content is preferably 5% to 55%, more preferably 6% to 35%, even more preferably 7% to 25%, and even more preferably 8% to 15%. In consideration of the coating performance, the viscosity of the resin composition solution is preferably in the range of 0.1 to 12000 cP, more preferably 0.5 to 10000, and even more preferably 1 to 8000 cP.
[0118] <Resin film> The resin film in the present invention can be prepared from the above resin composition. Specifically, the resin composition is applied to a substrate, and is dried, exposed to light, developed, and heat-treated, and cured to obtain a resin film having a fixed pattern, called a photosensitive resin film. In order to directly obtain a normal resin film, it is not necessary to carry out the exposure and development steps. When a normal resin film is further laminated, a protective film can be formed.
[0119] As the substrate, a silicon wafer, ceramics, gallium arsenide, an organic circuit board, an inorganic circuit board, a substrate obtained by forming a circuit-forming material on the substrate, or the like can be used, but the substrate is not limited to these.
[0120] The coating method may include spin coating, slit coating, dip coating, spraying, printing, etc., with the slit coating being preferred.
[0121] The drying method can be one of oven, hot plate, or infrared method, or some combination. The heating temperature is preferably 50°C to 180°C, and the heating time is preferably more than 30 seconds.
[0122] The exposure method includes covering the dried resin composition with a mask having a desired pattern and irradiating it with actinic radiation for exposure. The actinic radiation used for exposure includes ultraviolet light, visible light, electron beams, X-rays, etc., and the i-ray (365 nm), h-ray (405 nm), and g-ray (436 nm) of a mercury lamp are preferably used in the present invention. In order to form a heat-resistant resin pattern, the exposed portion is removed using a developer after exposure. After development, a photosensitive resin film can be obtained by utilizing heating and curing. The developer can be a well-known developer, and the development method can also be a well-known method.
[0123] The heat treatment and curing method can be one of oven, hot plate, and infrared method, and / or some combination of oven, hot plate, and infrared method. Considering the flatness, the heat treatment stage is divided into a first stage and a second stage, where during the first stage heat treatment and curing, the curing temperature is 120°C to 180°C, and the curing time is 2 minutes to 4 hours, and in this heat treatment and curing stage, the aromatic ester thermal crosslinking agent as the thermal crosslinking agent (b1) initiates the main crosslinking reaction, and the resin film can be pre-crosslinked to a controllable extent by the heat treatment and curing in the first stage to reduce the deformation of the resin film caused by the crosslinking reaction, and then during the second stage heat treatment and curing, the curing temperature is 180°C to 400°C, and the curing time is 2 minutes to 4 hours. The time is 2 minutes to 4 hours, in this heat treatment and curing stage, the heat crosslinking agent containing unsaturated bonds as the heat crosslinking agent (b2) starts the main crosslinking reaction, and the resin film is further crosslinked and cured by the heat treatment and curing in the second stage, so that a stable resin film can be formed. The crosslinking reaction in the first stage is not so violent that the crosslinking reaction in the second stage is effectively controlled by the large deformation of the resin film after development by the heat treatment and curing, so that the flatness of the photosensitive resin film after the heat treatment and curing can be better controlled. Considering the flatness of the obtained photosensitive resin film, in the heat treatment and curing conditions in the second stage, the maximum temperature is preferably less than 380°C, more preferably less than 350°C, and it is preferable to increase the temperature gradually in multiple stages during the temperature programming.
[0124] The resin film of the present invention includes a photosensitive resin film, a normal resin film, and a protective film, and can be applied not only to an organic EL display device but also to electronic parts such as a semiconductor device and a multilayer wiring board. In order to obtain good device performance, the thickness of the resin film is preferably 0.4 to 25 μm, more preferably 1.0 to 18 μm, and further preferably 1.5 to 12 μm.
[0125] <Display device> The present invention also provides a display device. Specifically, a normal resin film and / or a photosensitive resin film and / or a protective film obtained from the resin composition according to the present invention can be used for the planarization layer and / or the insulating layer in an organic EL display device having a driving circuit, a planarization layer, a first electrode, an insulating layer, a light-emitting layer and a second electrode on a substrate. An organic EL display device having long-term reliability and excellent bending recovery performance can be obtained.
[0126] The display device of the present invention can be bent and folded in any suitable manner, for example, the display device of the present invention can be bent either at the center of the photosensitive device or at the edge of the photosensitive device, and multiple types of bending can be realized at a specific portion of the display device according to the specific use and basic configuration, and can maintain long-term effective display properties.
[0127] <Example> Examples are listed below to illustrate the present invention, but the present invention is not limited thereto. First, abbreviations corresponding to some monomers contained in the examples are explained.
[0128] Compound 1: Diamine 5 (3,3'-dihydroxybenzidine, CAS No.: 2373-98-0)
[0129] [ka]
[0130] Compound 2: Acid dianhydride 1 (4,4'-oxydiphthalic anhydride, CAS No.: 1823-59-2)
[0131] [ka]
[0132] Compound 3: Acid dianhydride 2 (hexafluorodianhydride, CAS No.: 1107-00-2)
[0133] [ka]
[0134] Compound 4: Acid dianhydride 3 (p-phenylene-bis(trimellitate) dianhydride, CAS No.: 2770-49-2)
[0135] [ka]
[0136] Compound 5: Acid dianhydride 4 (3,3,4,4-diphenylsulfone-tetracarboxylic dianhydride, CAS No.: 2540-99-0)
[0137] [ka]
[0138] Compound 6: Acid dianhydride 5 (4,4'-(p-phenylenedioxy)bis(phthalic anhydride), CAS No.: 17828-53-4)
[0139] [ka]
[0140] Compound 7: Acid dianhydride 6 (3,3',4,4'-biphenyltetracarboxylic dianhydride, CAS No.: 2420-87-3)
[0141] [ka]
[0142] Compound 8: Thermal crosslinker (b1)-1 (4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol), CAS No.: 672926-26-0)
[0143] [ka]
[0144] Compound 9: Thermal crosslinker (b2)-1 (polydipentaerythritol hexaacrylate, CAS No.: 29570-58-9)
[0145] [ka]
[0146] Compound 10: Thermal crosslinker (b2)-2 (((methyl-1,3-phenylene)bis[iminoformyloxy[2,2-bis[[(1-oxoallyl)oxy]methyl]]-3,1-propanediyl]diacrylate), CAS No.: 51160-64-6)
[0147] [ka]
[0148] Compound 11: Thermal crosslinker (b2)-3 (4-(triisopropylsilylacetenyl)phenylacetylene, CAS No.: 75345-90-1)
[0149] [ka]
[0150] Compound 12: Siloxane compound 1 (SiDA, CAS No.: 2469-55-8)
[0151] [ka]
[0152] Compound 13: Siloxane compound 2 (2,2'-(1,1-diethyl-3,3-dimethyldisiloxane-1,3-diyl)bis(ethan-1-amine), CAS No.: 2152657-68-4)
[0153] [ka]
[0154] Compound 14: Esterification agent 1 (N,N-dimethylformamide diethyl acetal, CAS No.: 1188-33-6)
[0155] [ka]
[0156] Compound 15: Endcapping agent 1 (MAP, CAS No.: 591-27-5)
[0157] [ka]
[0158] Compound 16: Endcapping agent 2 (4-ethynylaniline, CAS No.: 14235-81-5)
[0159] [ka]
[0160] Compound 17: Solvent 1 (NMP, CAS No.: 872-50-4) Compound 18: Solvent 2 (GBL, CAS No.: 96-48-0) Synthesis Example 1 Diamine 1: N,N'-((perfluoropropane-2,2-diyl)bis(6-hydroxy-3,1-phenylene)bis(3-aminobenzamide))
[0161] [ka]
[0162] Step 1: 22g (0.06mol) of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 20.91g (0.36mol) of propylene oxide, and 120mL of acetone were added to a 1L reaction flask and stirred at room temperature until completely dissolved, then the reaction system was cooled to -15°C. Then, 120ml of acetone solution with 24.49g (0.132mol) of m-nitrobenzoyl chloride was added to the reaction system, and after the addition was completed, the mixture was kept under stirring at -15°C for 5 hours, and then allowed to warm to room temperature naturally. The resulting reaction solution was filtered under reduced pressure to obtain an off-white solid, and the solid was dried in a vacuum oven at 60°C for 20 hours.
[0163] Step 2: 20 g (0.03 mol) of the obtained off-white solid, 2.58 g of 5% palladium on carbon, and 170 mL of ethylene glycol methyl ether were added to a 500 mL high-pressure reactor, and the high-pressure reactor was replaced with hydrogen until the pressure in the reactor reached 10 kgf / cm. 2 The mixture was pressurized with hydrogen to reach 100% and stirred at 35° C. for 2 h. Then the pressure was slowly released and the reaction solution was filtered under reduced pressure to obtain a clear solution. Ethanol and petroleum ether were added to the solution, stirred for 6 h, and filtered to obtain a white solid. The solid was dried in a vacuum oven at 50° C. for 20 h to obtain diamine 1, i.e., N,N'-((perfluoropropane-2,2-diyl)bis(6-hydroxy-3,1-phenylene)bis(3-aminobenzamide)).
[0164] Synthesis Example 2 Diamine 2: N,N'-((perfluoropropane-2,2-diyl)bis(5-hydroxy-3,1-phenylene)bis(3-aminobenzamide))
[0165] [ka]
[0166] Step 1: 22 g (0.06 mol) of 2,2-bis(3-amino-5-hydroxyphenyl)hexafluoropropane, 20.91 g (0.36 mol) of propylene oxide, and 120 mL of acetone were added to a 1 L reaction flask and stirred at room temperature until completely dissolved, then the reaction was cooled to -15°C. Then, a solution of 24.49 g (0.132 mol) of 3-nitrobenzoyl chloride in acetone (120 ml) was slowly dripped into the reaction, and after the dripping was completed, the mixture was kept under stirring at -15°C for 5 hours, and then allowed to warm to room temperature naturally. The resulting reaction solution was filtered under reduced pressure to obtain an off-white solid, and the solid was dried in a vacuum oven at 60°C for 20 hours.
[0167] Step 2: 20 g (0.03 mol) of the obtained off-white solid, 2.58 g of 5% palladium on carbon, and 170 mL of ethylene glycol methyl ether were added to a 500 mL high-pressure reactor, and the high-pressure reactor was replaced with hydrogen until the pressure in the reactor reached 10 kgf / cm. 2 The mixture was pressurized with hydrogen to reach a pH of 10 and stirred at 35° C. for 2 h. Then, the pressure was slowly released and the reaction solution was filtered under reduced pressure to obtain a clear solution. Ethanol and petroleum ether were added to the solution, stirred for 6 h, and the solid precipitate was separated and filtered to obtain a white solid. The solid was dried in a vacuum oven at 50° C. for 20 h to obtain diamine 2, i.e., N,N'-((perfluoropropane-2,2-diyl)bis(5-hydroxy-3,1-phenylene)bis(3-aminobenzamide)).
[0168] Synthesis Example 3 Diamine 3: N,N'-(oxybis(6-hydroxy-5-(trifluoromethyl)-3,1-phenylene)bis(3-aminobenzamide))
[0169] [ka]
[0170] Step 1: 22.1 g (0.06 mol) of bis(3-trifluoromethyl-4-hydroxy-5-amino)phenyl ether, 20.91 g (0.36 mol) of propylene oxide, and 120 mL of acetone were added to a 1 L reaction flask and stirred at room temperature until completely dissolved, and then the reaction was cooled to -15°C. Then, a solution of 24.49 g (0.132 mol) of 3-nitrobenzoyl chloride in acetone (120 ml) was slowly dripped into the reaction, and after the dripping was completed, the mixture was kept under stirring at -15°C for 5 hours, and then allowed to warm to room temperature naturally. The resulting reaction solution was filtered under reduced pressure to obtain an off-white solid, and the solid was dried in a vacuum oven at 60°C for 20 hours.
[0171] Step 2: 20 g (0.03 mol) of the obtained off-white solid, 2.58 g of 5% palladium on carbon, and 170 mL of ethylene glycol methyl ether were added to a 500 mL high-pressure reactor, and the high-pressure reactor was replaced with hydrogen until the pressure in the reactor reached 10 kgf / cm. 2 The mixture was pressurized with hydrogen to reach 100% and stirred at 35° C. for 2 hours. The pressure was then slowly released and the reaction solution was filtered under reduced pressure to obtain a clear solution. Ethanol and petroleum ether were added to the solution, stirred for 6 hours, and the solid precipitate was separated and filtered to obtain a white solid. The solid was dried in a vacuum oven at 50° C. for 20 hours to obtain diamine 3, i.e., N,N'-(oxybis(6-hydroxy-5-(trifluoromethyl)-3,1-phenylene)bis(3-aminobenzamide)).
[0172] Synthesis Example 4 Diamine 4: 5,5'-(perfluoropropane-2,2-diyl)bis(2-(4-aminophenoxy)phenol)
[0173] [ka]
[0174] Step 1: 15.5g (0.06mol) of 2,2-bis(3-amino-4-hydroxyphenyl)dimethylpropane, 20.91g (0.36mol) of propylene oxide, and 140mL of acetone were added to a 1L reaction flask and stirred at room temperature until completely dissolved, then the reaction system was cooled to -15°C. Then, a solution of 24.49g (0.132mol) of m-nitrobenzoyl chloride in 140ml of acetone was slowly dripped into the reaction system, and after the dripping was completed, the mixture was kept under stirring at -15°C for 5 hours, and then allowed to warm to room temperature naturally. The resulting reaction solution was filtered under reduced pressure to obtain a white solid, and the solid was dried in a vacuum oven at 60°C for 20 hours.
[0175] Step 2: 14.9 g (0.03 mol) of the obtained white solid, 2.58 g of 5% palladium on carbon, and 170 mL of ethylene glycol methyl ether were added to a 500 mL high-pressure reactor, and the high-pressure reactor was replaced with hydrogen until the pressure in the reactor reached 10 kgf / cm. 2 The mixture was pressurized with hydrogen to reach a pressure of 1000 ml and stirred at 40° C. for 2 hours. The pressure was then slowly released and the reaction solution was filtered under reduced pressure to obtain a clear solution. Ethanol and petroleum ether were added to the solution, stirred for 6 hours, and the solid was separated and filtered to obtain a white solid. The solid was dried in a vacuum oven at 50° C. for 20 hours to obtain diamine 4, i.e., 5,5'-(perfluoropropane-2,2-diyl)bis(2-(4-aminophenoxy)phenol).
[0176] Synthesis Example 5 Photosensitizer 1: Diazidonaphthoquinone compounds
[0177] [ka]
[0178] Under the condition that the system is under nitrogen protection, 30.6g of 1,1,1-tris(4-hydroxyphenyl)ethane and 80.5g of 5-diazidonaphthoquinonesulfonyl chloride are added to 1,4-dioxane, the reaction system is warmed to 30°C, a mixed solution of 100g of 1,4-dioxane and 13.3g of triethylamine is added dropwise, the system is maintained at a temperature of 30°C and stirred for 3 hours, the reaction solution is filtered to remove triethylamine salt, the filtrate is added dropwise to purified water to separate the solid, the solution is filtered, the precipitate is collected and dried in a vacuum oven to obtain photosensitizer 1, i.e., diazidonaphthoquinone compound.
[0179] Synthesis Example 6: Synthesis of Resin (a-1) Under the condition that the system was under nitrogen protection, 0.09 mol of 5,5'-(perfluoropropane-2,2-diyl)bis(2-(4-aminophenoxy)phenol) (diamine 4) obtained in Synthesis Example 4 and 0.05 mol of MAP (endcapping agent 1) were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 4,4'-oxydiphthalic anhydride (acid dianhydride 1) was added to the reaction solution in the oil bath and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-1).
[0180] Synthesis Example 7: Synthesis of Resin (a-2) Under the condition that the system was under nitrogen protection, 0.085 mol of N,N'-((perfluoropropane-2,2-diyl)bis(6-hydroxy-3,1-phenylene)bis(3-aminobenzamide)) (diamine 1) obtained in Synthesis Example 1, 0.005 mol of SiDA, and 0.05 mol of MAP (endcapping agent 1) were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 4,4'-oxydiphthalic anhydride (acid dianhydride 1) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-2).
[0181] Synthesis Example 8: Synthesis of Resin (a-3) Under the condition that the system was under nitrogen protection, 0.085 mol of N,N'-((perfluoropropane-2,2-diyl)bis(6-hydroxy-3,1-phenylene)bis(3-aminobenzamide)) (diamine 1) obtained in synthesis example 1, 0.005 mol of SiDA, and 0.05 mol of MAP (endcapping agent 1) were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of hexafluorodianhydride (acid dianhydride 2) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-3).
[0182] Synthesis Example 9: Synthesis of Resin (a-4) Under the condition that the system was under nitrogen protection, 0.085 mol of N,N'-((perfluoropropane-2,2-diyl)bis(6-hydroxy-3,1-phenylene)bis(3-aminobenzamide)) (diamine 1) obtained in synthesis example 1, 0.005 mol of SiDA, and 0.05 mol of MAP (endcapping agent 1) were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of p-phenylene-bis(trimellitate) dianhydride (acid dianhydride 3) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-4).
[0183] Synthesis Example 10: Synthesis of Resin (a-5) Under the condition that the system was under nitrogen protection, 0.085 mol of N,N'-((perfluoropropane-2,2-diyl)bis(5-hydroxy-3,1-phenylene)bis(3-aminobenzamide)) (diamine 2) obtained in synthesis example 2, 0.005 mol of SiDA, and 0.05 mol of endcapping agent MAP (endcapping agent 1) were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 3,3,4,4-diphenylsulfone-tetracarboxylic dianhydride (acid dianhydride 4) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-5).
[0184] Synthesis Example 11: Synthesis of Resin (a-6) Under the condition that the system was under nitrogen protection, 0.085 mol of N,N'-(oxybis(6-hydroxy-5-(trifluoromethyl)-3,1-phenylene)bis(3-aminobenzamide)) (diamine 3) obtained in Synthesis Example 3, 0.005 mol of SiDA, and 0.05 mol of end-capping agent MAP were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 4,4'-(p-phenylenedioxy)bis(phthalic anhydride) (acid dianhydride 5) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-6).
[0185] Synthesis Example 12: Synthesis of Resin (a-7) Under the condition that the system was under nitrogen protection, 0.085 mol of 5,5'-(perfluoropropane-2,2-diyl)bis(2-(4-aminophenoxy)phenol) (diamine 4) obtained in synthesis example 4, 0.005 mol of SiDA, and 0.05 mol of endcapping agent MAP were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 4,4'-(p-phenylenedioxy)bis(phthalic anhydride) (acid dianhydride 5) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-7).
[0186] Synthesis Example 13: Synthesis of resin (a-8) Under the condition that the system was under nitrogen protection, 0.085 mol of N,N'-((perfluoropropane-2,2-diyl)bis(6-hydroxy-3,1-phenylene)bis(3-aminobenzamide)) (diamine 1) obtained in Synthesis Example 1, 0.005 mol of SiDA, and 0.05 mol of 4-ethynylaniline (endcapping agent 2) were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 4,4'-oxydiphthalic anhydride (acid dianhydride 1) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterification agent, was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-8).
[0187] Synthesis Example 14: Synthesis of Resin (a-9) Under the condition that the system was under nitrogen protection, 0.085 mol of N,N'-((perfluoropropane-2,2-diyl)bis(6-hydroxy-3,1-phenylene)bis(3-aminobenzamide)) (diamine 1) obtained in synthesis example 1, 0.005 mol of 2,2'-(1,1-diethyl-3,3-dimethyldisiloxane-1,3-diyl)bis(ethan-1-amine) (siloxane compound 2), and 0.05 mol of endcapping agent MAP were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 4,4'-oxydiphthalic anhydride (acid dianhydride 1) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of N,N-dimethylformamide diethyl acetal, an esterifying agent, was added and stirred for 3 hours, the mixture was poured into 2 L of water, filtered, and the product was washed three times. The product was dried at 50° C. for 72 hours using a vacuum dryer to obtain resin (a-9).
[0188] Synthesis Example 15: Synthesis of Resin (a-10) Under the condition that the system was under nitrogen protection, 0.085 mol of 3,3'-dihydroxybenzidine (diamine 5) and 0.05 mol of the end-capping agent MAP were dissolved in 500 mL of NMP. After stirring and dissolving, the mixture was heated in an oil bath at 60 ° C. 0.1 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (acid dianhydride 6) was added to the reaction solution and reacted for 2 hours. Then, 5.0 mol of the esterification agent N,N-dimethylformamide diethyl acetal was added and stirred for 3 hours, the mixture was put into 2 L of water, filtered, and the product was washed three times. The product was dried at 50 ° C. for 72 hours using a vacuum dryer to obtain resin (a-10).
[0189] The synthesis ratios of polymer (a) in Synthesis Examples 6 to 15 are shown in Table 1. [Table 1]
[0190] [Table 1-1]
[0191] [Table 1-2]
[0192] [Table 1-3]
[0193] Example 1 10 g of the resin (a-1) obtained in Synthesis Example 6 above was weighed out and added to 150 g of GBL solvent, followed by 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of polydipentaerythritol hexaacrylate (thermal crosslinker (b2)-1), and 3 g of a quinone diazide compound, which is a photosensitizer, and the mixture was stirred for 1 hour to obtain slurry 1. The effects of the obtained slurry were evaluated, and the results are shown in Table 3.
[0194] Example 2 10 g of the resin (a-2) obtained in Synthesis Example 7 above was weighed out and added to 150 g of GBL solvent, followed by 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of polydipentaerythritol hexaacrylate (thermal crosslinker (b2)-1), and 3 g of a quinone diazide compound, which is a photosensitizer, and the mixture was stirred for 1 hour to obtain slurry 2. The effects of the obtained slurry were evaluated, and the results are shown in Table 3.
[0195] Example 3 10 g of the resin (a-2) obtained in the above synthesis example 7 was weighed and added to 150 g of GBL solvent, and then 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of (methyl-1,3-phenylene)bis[iminoformyloxy[2,2-bis[[(1-oxoallyl)oxy]methyl]]-3,1-propanediyl]diacrylate (thermal crosslinker (b2)-2), and 3 g of a quinone diazide compound, which is a photosensitizer, were added, and the mixture was stirred for 1 hour to obtain slurry 3. The effect of the obtained slurry was evaluated, and the results are shown in Table 3.
[0196] Example 4 10 g of the resin (a-3) obtained in Synthesis Example 8 above was weighed out and added to 150 g of GBL solvent, followed by 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of polydipentaerythritol hexaacrylate (thermal crosslinker (b2)-1), and 3 g of a quinone diazide compound, which is a photosensitizer, and the mixture was stirred for 1 hour to obtain slurry 4. The effects of the obtained slurry were evaluated, and the results are shown in Table 3.
[0197] Example 5 10 g of the resin (a-4) obtained in Synthesis Example 9 above was weighed out and added to 150 g of GBL solvent, followed by 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of polydipentaerythritol hexaacrylate (thermal crosslinker (b2)-1), and 3 g of a quinone diazide compound, which is a photosensitizer, and the mixture was stirred for 1 hour to obtain slurry 5. The effects of the obtained slurry were evaluated, and the results are shown in Table 3.
[0198] Example 6 10 g of the resin (a-5) obtained in the above synthesis example 10 was weighed and added to 150 g of GBL solvent, and then 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of (methyl-1,3-phenylene)bis[iminoformyloxy[2,2-bis[[(1-oxoallyl)oxy]methyl]]-3,1-propanediyl]diacrylate (thermal crosslinker (b2)-2), and 3 g of a quinone diazide compound, which is a photosensitizer, were added, and the mixture was stirred for 1 hour to obtain slurry 6. The effect of the obtained slurry was evaluated, and the results are shown in Table 3.
[0199] Example 7 10 g of the resin (a-6) obtained in the above Synthesis Example 11 was weighed out and added to 150 g of GBL solvent, and then 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of polydipentaerythritol hexaacrylate (thermal crosslinker (b2)-1), and 3 g of a quinone diazide compound, which is a photosensitizer, were added, and the mixture was stirred for 1 hour to obtain slurry 7. The effects of the obtained slurry were evaluated, and the results are shown in Table 3.
[0200] Example 8 10 g of the resin (a-7) obtained in the above synthesis example 12 was weighed and added to 150 g of GBL solvent, and then 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of (methyl-1,3-phenylene)bis[iminoformyloxy[2,2-bis[[(1-oxoallyl)oxy]methyl]]-3,1-propanediyl]diacrylate (thermal crosslinker (b2)-2), and 3 g of a quinone diazide compound, which is a photosensitizer, were added, and the mixture was stirred for 1 hour to obtain a slurry 8. The effect of the obtained slurry was evaluated, and the results are shown in Table 3.
[0201] Example 9 10 g of the resin (a-7) obtained in Synthesis Example 12 above was weighed out and added to 150 g of GBL solvent, followed by 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of polydipentaerythritol hexaacrylate (thermal crosslinker (b2)-1), and 3 g of a quinone diazide compound, which is a photosensitizer, and the mixture was stirred for 1 hour to obtain slurry 9. The effects of the obtained slurry were evaluated, and the results are shown in Table 3.
[0202] Example 10 10 g of the resin (a-8) obtained in the above Synthesis Example 13 was weighed out and added to 150 g of GBL solvent, and then 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of 4-(triisopropylsilylacetenyl)phenylacetylene (thermal crosslinker (b2)-3), and 3 g of a quinone diazide compound, which is a photosensitizer, were added, and the mixture was stirred for 1 hour to obtain a slurry 10. The effect of the obtained slurry was evaluated, and the results are shown in Table 3.
[0203] Example 11 10 g of the resin (a-9) obtained in the above synthesis example 14 was weighed out and added to 150 g of GBL solvent, and then 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of 4-(triisopropylsilylacetenyl)phenylacetylene (thermal crosslinker (b2)-3), and 3 g of a quinone diazide compound, which is a photosensitizer, were added, and the mixture was stirred for 1 hour to obtain slurry 11. The effect of the obtained slurry was evaluated, and the results are shown in Table 3.
[0204] Comparative Example 1 10 g of the resin (a-10) obtained in Synthesis Example 15 above was weighed out and added to 150 g of GBL solvent, followed by 2 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1), 0.11 g of polydipentaerythritol hexaacrylate (thermal crosslinker (b2)-1), and 3 g of a quinone diazide compound, which is a photosensitizer, and the mixture was stirred for 1 hour to obtain slurry 12. The effects of the obtained slurry were evaluated, and the results are shown in Table 3.
[0205] Comparative Example 2 10 g of the resin (a-2) obtained in Synthesis Example 7 above was weighed out and added to 150 g of GBL solvent, followed by the addition of 2.11 g of 4,4',4''-(ethane-1,1,1-triyl)tris(2,6-bis(methoxymethyl)phenol) (thermal crosslinker (b1)-1) and 3 g of a quinone diazide compound as a photosensitizer, and the mixture was stirred for 1 hour to obtain slurry 13. The effect of the obtained slurry was evaluated, and the results are shown in Table 3.
[0206] Comparative Example 3 10 g of the alkali-soluble resin (a-2) obtained in the above Synthesis Example 7 was weighed out and added to 150 g of GBL solvent, then 2.11 g of polydipentaerythritol hexaacrylate (thermal crosslinking agent (b2)-1) and 3 g of a quinone diazide compound as a photosensitizer were added, and the mixture was stirred for 1 hour to obtain slurry 14. The effect of the obtained slurry was evaluated, and the results are shown in Table 3.
[0207] The synthesis ratios for the slurries in Examples 1 to 11 and Comparative Examples 1 to 3 are shown in Table 2. [Table 2]
[0208] [Table 2-1]
[0209] [Table 2-2]
[0210] Performance Test Method In the examples, the molecular weight of the resin composition can be tested by a conventional GPC, the viscosity can be tested by an E-type viscometer, and the film thickness can be tested by a conventional film thickness meter. The evaluation of the resin film formed from the resin composition was carried out according to the following method.
[0211] 1. Evaluation method for thermal crosslinking group: Thermomechanical analysis (TMA) was used in the present invention to test the glass transition temperature Tg (apparatus model: DSC3500, Netzsch), and methods such as dynamic mechanical analysis (DMA) and differential scanning calorimeter (DSC) may also be used for testing. The specific method was as follows: The prepared varnish was spin-coated, dried, exposed, developed, heat-treated, and cured to obtain a photosensitive resin film with a film thickness of 5 μm±0.1 μm, and then the photosensitive resin film was prepared into a sample for thermomechanical analysis testing, and the sample was tested to determine the Tg. g The value was obtained.g represents the kinetic properties of the molecular chain portion. The larger the Tg value, the smaller the kinetic properties of the molecular chain portion, i.e., the better the degree of thermal crosslinking. T g At 335℃ or higher, the degree of thermal crosslinking is excellent and is evaluated as ○, and T g When Tg was 325 to 335°C, the degree of thermal crosslinking was good and was evaluated as △, and when Tg was 325°C or lower, the degree of thermal crosslinking was poor and was evaluated as ×.
[0212] 2. Evaluation method for flatness index: CD-SEM (equipment model: SU3500 from Hitachi High-Technologies Corporation) was used in the present invention to test the flatness index. The specific method was as follows: The prepared varnish was spin-coated and pre-dried to a film thickness of 4 μm±0.1 μm, then exposure and development processes were carried out, then the film thickness was tested as h1, then heat treatment and curing processes were carried out, then the film thickness was tested as h2, and h1 and h2 were tested by CD-SEM. The flatness index (%) was calculated according to the following formula (1). The larger the flatness index, the larger the shrinkage deformation of the film during heat treatment and curing, and the worse the flatness. The smaller the flatness index, the smaller the shrinkage deformation of the film during heat treatment and curing, and the better the flatness. The flatness ultimately affected the properties such as efficiency, yield, and service life in the equipment. If the flatness index was 25% or less, the flatness was evaluated as excellent and represented as ◯, if the flatness index was 25%-35%, the flatness was evaluated as good and represented as △, and if the flatness index was 35% or more, the flatness was evaluated as poor and represented as ×. Flatness index (%)=(h1-h2) / h1×100% Equation (1)
[0213] 3.Flexibility index rating: A tensile tester (equipment model: RTG1210 from Tensilon) was used in the present invention to test the mechanical properties of the film. The specific method was as follows: The prepared varnish was spin-coated, dried, heat-treated, and cured to obtain a normal resin film with a film thickness of 5 μm±0.1 μm, and then the normal resin film was prepared into a sample strip for tensile testing, and the data of tensile strength, elongation, and Young's modulus were obtained. The tensile strength indicated the degree of sensitivity to breakage when stress deformation occurs, and the larger the tensile strength, the better. The elongation indicated the degree of elongation movement of the molecular chain when stress deformation occurs. When the elongation was too small, the elongation movement of the molecular chain was very small / very difficult, that is, almost no elastic deformation occurred. When the elongation was too large, plastic deformation occurred easily, and recovery was difficult when stress deformation occurred. Only when the elongation was within a certain range, it could lead to bending recovery. Young's modulus indicates the stiffness of the material, i.e., if the stiffness is too large, little stress deformation occurs, and if the stiffness is too small, plastic deformation occurs easily, which makes recovery after deformation difficult. Therefore, only when the Young's modulus is within a certain range can it lead to bending recovery. That is, the flexibility index also reflects bending recovery performance. When the tensile strength was 120 MPa or more, the elongation range was between 5% and 28%, and the Young's modulus range was between 0.5 GPa and 9.0 GPa, the flexibility index was excellent and rated as ◎; when the tensile strength was 90 MPa to 120 MPa, the elongation range was between 5% and 28%, and the Young's modulus range was 0.5 GPa to 9.0 GPa, the flexibility index was good and rated as ○; when the tensile strength was 90 MPa or more, the elongation was 28% or more or 2% or less, the Young's modulus was 9.0 GPa or more or 0.5 GPa or less, the flexibility index was moderate and rated as △; and when the tensile strength was 90 MPa or less, the flexibility index was poor and rated as ×.
[0214] The evaluation results of Examples 1 to 11 and Comparative Examples 1 to 3 are shown in Table 3. [Table 3]
[0215] [Table 3]
[0216] According to the evaluation results of Examples 1 to 11 and Comparative Examples 1 to 3 in Table 3, Examples 2 to 4 and 6 had excellent thermal crosslinking degree evaluation, flatness index evaluation and flexibility index. In other words, the resin compositions in Examples 2 to 4 and 6 could result in better flatness and bending recovery performance, which was ideal.
[0217] For Example 1, Example 5, and Example 7 to Example 9, the thermal crosslinking degree evaluation was excellent, the flatness index evaluation was excellent or good, and the flexibility index was rated as good, and Example 1, Example 5, and Example 7 to Example 9 were slightly worse than the ideal Examples 2 to 4 and Example 6 in terms of both flatness index evaluation performance and flexibility index. For Example 10 and Example 11, the thermal crosslinking degree evaluation was good, the flatness index evaluation was excellent, and the flexibility index was rated as better, and the thermal crosslinking degree evaluation was worse than the ideal thermal crosslinking degree evaluation of Example 1 to Example 9, but the better flexibility index was maintained. Thus, compared to Example 2 to Example 4 and Example 6, Example 1, Example 5, and Example 7 to Example 11 are quasi-ideal.
[0218] For Comparative Examples 1 to 3, the thermal crosslinking degree evaluation was rated as good or poor, the flatness index evaluation was rated as good or poor, and the flexibility index was rated as moderate, and compared with Examples 1 to 11, the overall performance was poor and not ideal.
Claims
1. A resin composition comprising at least three components, namely, components (a), (b) and (c), wherein the component (a) is a polymer having a structure represented by the following formula (1), the component (b) comprises a thermal crosslinking agent (b1) and a thermal crosslinking agent (b2), the thermal crosslinking agent (b1) is an aromatic phenol thermal crosslinking agent, and the thermal crosslinking agent (b2) is a thermal crosslinking agent containing an unsaturated bond; The component (c) is a photosensitizer, 【Chemistry 1】 In the formula, R 1 is -O-, -SO 2 -, -NH-, -CO-, -Si-O-, 【Chemistry 2】 is selected from R 2 teeth, 【Chemistry 3】 is selected from R 3 and R 4 are independently selected from a hydrogen atom or an organic group having 1 to 20 carbon atoms, and n is an integer selected from 1 to 10; The thermal crosslinking agent (b1) is a low-temperature thermal crosslinking compound having a thermal crosslinking temperature of 120°C to 180°C, and is selected from the structures represented by the following formula (2): 【Chemistry 4】 wherein R 8 is selected from an organic group containing 2 to 30 carbon atoms, R 9 is selected from an organic group containing 1 to 10 carbon atoms, s is an integer selected from 1 to 4, p is an integer selected from 1 to 16, and s+p>2; The thermal crosslinking agent (b2) is a thermal crosslinking compound having a thermal crosslinking temperature of 180° C. to 400° C., and is selected from the structures represented by the following formula (3): 【Chemistry 5】 wherein R 6 is independently selected from an organic group containing at least 2 to 30 carbon atoms; and y is independently an integer selected from 1 to 10; The resin composition, wherein the photosensitizer of the component (c) is a photoacid generator.
2. The component (a) is a polymer having a structure represented by the following formula (6): 【Chemistry 6】 In the formula, R 1 and R 2 is independently selected from the group containing at least one atom other than hydrogen, R 3 and R 4 are independently selected from a hydrogen atom or an organic group having 1 to 20 carbon atoms; R 5 is selected from halogen and / or halogenated hydrocarbyl, and / or organic groups having 1 to 10 carbon atoms; n and m are independently integers selected from 1 to 10; The resin composition according to claim 1.
3. 3. The resin composition of claim 1 or claim 2, further comprising one or more of a polyamide, a polyimide, a polyimide precursor, a polybenzoxazole, a polybenzoxazole precursor, or a copolymer thereof.
4. The resin composition according to any one of claims 1 to 3, further comprising a phenolic hydroxyl compound.
5. A photosensitive resin film prepared from the resin composition according to claim 1.
6. A display device prepared from the photosensitive resin precursor composition according to claim 1.
Citation Information
Patent Citations
Photosensitive resin composition and metal-resin complex using same
JP2007264028A
Resin composition, resin sheet, cured film, production method of cured film, semiconductor device and display device
JP2020066651A
Diamine compound, and heat-resistant resin or heat-resistant resin precursor in which same is used
WO2018029746A1
Resin composition, cured film, semiconductor device and method for producing same
WO2018066395A1
Negative-type photosensitive resin composition, cured film, and organic el display and manufacturing method therefor
WO2019087985A1